INTEGRASI NILAI-NILAI EKOTEOLOGI MELALUI PEMANFAATAN KEBUN MADRASAH DI MIN 1 KULON PROGO (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the integration of eco-theological values through the use of madrasah gardens as a learning medium at MIN 1 Kulon Progo. This study responds to the demands of 21st-century education, which not only emphasizes the development of cognitive aspects and digital literacy but also the formation of character, ecological awareness, and spiritual responsibility of students. Ecotheological studies in Islamic education have so far been dominated by normative and conceptual approaches, thus requiring empirical studies that reveal their implementation in educational practices in madrasahs. The madrasah garden in this study is conceptualized as a living laboratory that integrates science learning, the formation of ecological attitudes, and the contextual internalization of faith values in daily activities. This study uses a qualitative approach with a case study design. The research subjects include madrasah principals, teachers, and students involved in the management and utilization of madrasah gardens. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation, then analyzed thematically through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the madrasah garden not only functions as a means of practicing plant cultivation, but also as a medium for internalizing the values of monotheism, trust, responsibility, and care for Allah's creation. This integration results in a concrete, contextual, and transformative learning experience for students.